Perturbation results on the zero-locus of a polynomial. (May 2017) - Torrente, Maria-Laura; Beltrametti, Mauro C.; Sommese, Andrew J.
Abstract: Let f and g be complex multivariate polynomials of the same degree. Extending Beauzamy's results which hold in the univariate case, we bound the Euclidean distance of points belonging to the zero-loci of f and g in terms of the Bombieri norm of the difference g − f . We also discuss real perturbations of real polynomials.